LEARNING THROUGH DISCUSSION: A STUDY TO FOSTER STUDENTS' ENGAGEMENT IN EFL CLASS - Mita Nur Aflah; Rafika Nurhidayah; Hendro Kuncoro (Jurnal Ilmiah Spectral, 2023)
This research aims to foster students' engagement through small group discussions. The focus is on implementing group discussion strategies on classroom performance and students' achievement. A qualitative design was used along with the observations and interviews, and enriched with a small group discussion teaching framework. The result showed that small group discussions positively contribute to students' involvement in the classroom, enhance critical thinking, and raise motivation. The activities provide opportunities to increase their upbeat view of learning English. Hopefully, the result can be a practical suggestion for lecturers or teachers to maximize the students' active participation in ELF classes.